FACILITY MANAGER’S ACCEPTANCE OF CMMS IN MALAYSIA: AN EXPLORATORY STUDY USING PLS-SEM APPROACH - Abu Bakar, Zulazhan; Kamaruzzaman, Syahrul Nizam (Journal of Surveying, Construction and Property, 2023)
Computerised Maintenance Management System (CMMS) is a widely recognised software in Facilities Management (FM) that provides numerous advantages to facility managers by enhancing productivity at work. The objective of this research is to provide insight and assess the factors influencing the acceptance of CMMS among facility managers in Malaysia. As a result, an improved comprehension of CMMS technology acceptance can be formed, as well as a better understanding of other FM technology adoption. Multiple factors influence CMMS acceptance, and this study used a quantitative technique to verify the hypothesis, using the Technology Acceptance Model (TAM) in conjunction with a Partial Least Square-Structural Equation Model (PLS-SEM). In addition, 125 facility managers completed an online survey that was utilised to collect primary data. The quantitative and structural models were analysed using PLS-SEM. Based on the study's findings, perceived usefulness (PU) and perceived ease of use (PEOU) have a favourable impact on behavioural intention (BI), which influences actual usage (AU) of CMMS. The research aims to improve awareness of the degree of acceptance of CMMS among facility managers and to contribute to FM organisations' better understanding of future technology adoptions.